AKIBAT HUKUM TERHADAP KREDITUR LAIN APABILA SALAH SATU KREDITUR MENGAJUKAN PERNYATAAN PAILIT (DUE TO THE LAW ON THE OTHER CREDITORS IF ONE OF CREDITORS SUBMITTING STATEMENT PAILI T) - Herry Anto Simanjuntak (Universitas Quality, 2020)
In everyday life today, both individuals (natural p erson ) nor a legal person (legal entity) sometimes do not have enough money to finance your exit so that a person or legal entity obtaining loans from people or legal entities to carry out activities where the parties obtain the loan called the debtor while the party providing the loan is called a creditor. In general, creditors provide loans to debtors is based on the trust (trust) that the debtor will return the loan on time, so the first factor that is considered by the creditor is willingness (willigness)) from the debtor to return the debt. From this description confidence (trust) is a major key creditor to deb it ur to provide pinjamannnya or so-called credit by making the agreement document, but with the passage of time in practice were encountered where the debtor can not repay the loan it to the creditor , the state is usually caused because of financial distress from the debtor's business that has suffered a setback, resulting in the debtor being declared bankrupt. In declaring a debtor to be declared bankrupt there must be a court decision which results in general confiscation of all assets of the existing and future bankrupt debtors. The management and settlement of bankruptcy are carried out by the curator under the supervision of a supervising judge with the main purpose of using the proceeds of the sale of assets to pay all debts of the bankrupt debtor proportionally (in accordance with the prorate parte) or in accordance with the creditor's structure.